Column Performance in Lead(II) Removal from Aqueous Solutions by Fixed-bed Column of Mango Wood Sawdust (Mangifera indica) - Miranti Puspitasari (Jurnal Kimia Riset, 2018)
AbstractThe contamination of water resources due to the exceed Pb content is becoming an environmental serious problem. Adsorption method in dynamic system using fixed bed column can be used to reduce the level of Pb in an attempt to suppress the toxic effects caused by Pb. This study aims to optimize the parameters of Pb adsorption on samples by mango wood sawdust in a dynamic system. Mango wood sawdust was activated by HNO3 and ethanol then packed in a column. Optimization of adsorption parameters including adsorbent heating temperature, adsorbent mass, pH of the influen solution, and the influen flow rate. The experiment result showed that the optimum conditions of mango wood sawdust to reducing Pb in samples are adsorbent was heated at temperature 145°C, using 3 grams adsorbent packed in a column, and the influen solution at pH 7 was passed at a flow rate 1 mL/min. Adsorption capacity of mango wood sawdust in reducing Pb in samples at optimum condition is equal to 14.8 mg/g of adsorbent and types of adsorption that occurs between the adsorbent with adsorbate is chemical adsorption . Keywords: Adsorption, dynamic system, fixed-bed column, mango wood sawdust, lead metal